Cross-cultural adaptation and reliability of Positive and Negative Affect Schedule (PANAS) on Thai smokers - Klinsophon, Thaniya; Thaveeratitham, Premtip; Janwantanakul, Prawit (Chulalongkorn Medical Journal, 2023)
Background : Positive and Negative Affect Schedule (PANAS) is a questionnaire for evaluating the affect which is one of the factors associated with smoking relapse and is widely used in clinics and in research. The original version of PANAS is in English and has been translated into many languages. However, there has been no translation available into the Thai language. Objectives : To translate PANAS into the Thai language by using the standard method according to the cross-cultural adaptation process and to evaluate the test-retest reliability and internal consistency of PANAS in Thai smokers. Methods : PANAS was translated into Thai. Participants – current smokers – completed the questionnaire twice, at baseline and seven days after. The intra-class correlation coefficient (ICC (3, 1)) and Cronbach’s alpha were calculated for the test-retest reliability and internal consistency, respectively. Results : The average age of 60 participants was 35.2 years old. They averagely smoked 10.9 cigarettes per day over an average period of 12.9 years. Sixty-five percent of the participants had previously attempted to quit. The ICC (3, 1) of PANAS in Thais was 0.90 for positive affect and 0.93 for negative affect. Cronbach’s alpha was 0.89 for positive affect and 0.90 for negative affect. Conclusion : In general, PANAS in Thai demonstrated good to excellent internal consistency and excellent test-retest reliability. Therefore, the PANAS in Thai could be used in clinics and in researches.